Hubungan Sikap, Perilaku, dan Pengetahuan Gizi Orang Tua terhadap Pemilihan Camilan Sehat pada Anak Usia Dini di TK Aisyiyah 3 Lasem - Monika Yunia Putri Riyanti; Herry Susanto; Indra Tri Astuti (Journal of Medical Practice and Research, 2025)
The selection of healthy snacks in early childhood plays a crucial role in developing good eating habits. Parents play a key role in determining the types of snacks given to children. This study aimed to determine the relationship between parental attitudes, behaviors, and nutritional knowledge and healthy snack choices among children at TK Aisyiyah 3 Lasem. The study used a cross-sectional design, with 114 parent and children  respondents selected through total sampling. The research instrument used the BAQ-HH questionnaire, which had been developed and tested for validity and reliability. Data were analyzed univariately, bivariately using the Chi-Square test, and multivariately using binary logistic regression. The study showed that most parents had good knowledge (71.1%), positive attitudes (44.7%), and good behavior (68.4%), but the selection of healthy snacks for children was not optimal, where 57.9% were in the good category and 42.1% were still poor. Bivariate analysis showed a significant relationship between parental attitudes and the choice of healthy snacks (p = 0.007). However, no significant relationship was found between behavior (p = 0.078) or knowledge (p = 0.869) with the choice of healthy snacks. The results of the multivariate analysis showed that behavior was the most dominant factor in the choice of healthy snacks for children, where parents with poor behavior where 112 times more likely to choose unhealty snacking (OR= 112,664; p= 0,004).